Robust passive adaptive fault tolerant control for stochastic wing flutter via delay control. (July 2019) - Li, Ning; Sun, Haiyi; Zhang, Qingling
Highlights: The model of this manuscript is a more general LOE–LIP flutter model and covers several common fault tolerant situations. The designed observer of this manuscript can compensate both the nonlinear uncertainty and the Itô differential item. The robust passive adaptive fault tolerant controller based on the observer is constructed to solve the wing flutter problem. Abstract: The problem of robust passive adaptive fault tolerant control for the stochastic wing flutter model is studied in this paper. The stochastic wing flutter model considered possesses the control delay, disturbances, external stochastic bounded disturbance, loss of effectiveness (LOE) and lock-in-place (LIP). The proposed model is a more general LOE–LIP flutter model and covers several common actuator fault tolerant situations. A fault tolerant flutter adaptive observer is given to provide the information of wing flutter states. By combining stability theory of stochastic differential equation, Lyapunov method, adaptive control principles, and linear matrix inequalities (LMIs) technique, the robust passive adaptive fault tolerant controller based on the observer is constructed to solve the wing flutter problem. The passivation of the closed-loop system is theoretically proved. The passive control design for the wing flutter model has its practical significance. The controller can improve the robustness of the closed-loop system, and it accords with the real situation of aeroelastic system. Finally, the applicability and correctness of the proposed controller is well carried out by simulation examples.